Kebijakan Lingkungan dalam Menanggapi Permasalahan Perubahan Iklim di Indonesia: Sebuah Tinjauan Integratif - Getah Ester Hayatulah; Jamaluddin Mahasari; Muhammad Ihsan; Muhammad Bagus Adi Wicaksono; Syukra Alhamda (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Climate change can cause problems for humans if not handled properly. Therefore, the government as the authority needs to make policies in dealing with problems caused by climate change. This research then aims to look at the environmental policies that have been or can be implemented by the Indonesian government in overcoming the problem of climate change. This research will be carried out using a descriptive qualitative approach. The results of this study then found that in addition to national policies through the National Action Plan for Reducing Greenhouse Gas Emissions (RAN-GRK) and the Climate Change Adaptation Plan (RAN API), the Indonesian government also contributed to agreements and international cooperation to be able to overcome the impacts from climate change. Capacity building, technology transfer, and development of sustainable financing mechanisms are also important aspects of regional and international cooperation. Other policies that can be implemented by the Indonesian government are building education to increase public awareness and understanding of climate change and implementing information campaign initiatives to increase public participation in climate change mitigation and adaptation efforts.